Restorative Justice in Juvenile Justice: A Comparative Study - Abdulrazaq Khlaf, Lect. Samia (Basra studies journal, 2024)
Modern criminal policy is increasingly adopting clear trends outlined by international rules and endorsed by most countries, incorporating them into national legislation. The primary aim of these policies is to protect juveniles from crime and prevent recidivism. These rules advocate viewing the juvenile not as a criminal deserving punishment, but as a victim of social circumstances that led to their delinquency. Despite all the efforts made by the traditional criminal justice system to ensure the rights of juveniles, it remains inadequate in providing optimal solutions to address juvenile delinquency, which has been on the rise recently, with some forms taking on the character of organized crime. This necessitates different approaches than those used in the traditional criminal justice system. As a result, a new judicial approach has emerged, known as restorative justice or reformative justice. This approach is enshrined in some international agreements, such as the 1990 Convention on the Rights of the Child, among others. These agreements emphasize the need to transition from formal judicial procedures to alternative measures where appropriate and to reintegrate children into society. Restorative justice involves a meeting between the offender and the victim, sometimes in the presence of community representatives, to discuss the offense and attempt to reach a collective opinion on what the offender should do to compensate the victim for the harm caused. This compensation could be monetary, a moral apology, community service, or any other form of reparation, recognizing that crime is a breach of human relationships and affects the offender, the victim, and the community. Finally, we hope that the Iraqi legislator will adopt the findings and recommendations of this research and attempt to integrate the traditional criminal justice system with restorative justice, similar to some other legislations. This integration could help reduce juvenile crime and delinquency, save the state effort and money, and achieve public benefit.